Using Digital Storytelling to Shape Student’s Prosocial Behavior: Is it Effective? - Bawono, Yudho; Purwo Wibowo, Wasis; Hawarin Akmalia, Layutsa; Amirotin, Shofiyah; Andini, Intan (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
The purpose of this study was to determine the effectiveness of providing digital storytelling on the prosocial behavior of elementary school-aged children. The study employed a pre-experimental design with one group pretest-posttest. The treatment given was the provision of digital storytelling. This digital storytelling was taken from the YouTube video sharing platform, “Riri Cerita Anak Interaktif”. This study was a total population study with the research population being all fifth-grade students of As Salam Elementary School, Bangkalan Regency. The method used to collect data was by administering Prosocial Tendencies Measure-Revised (PTM-R). The data were analyzed using SPSS 26.0 for Windows with Paired Sample t-Test. Based on the output table Paired Samples t-Test, the Sig value is known (2-tailed) is 0.001 < 0.05, then H0 is rejected and Ha is accepted. So it can be concluded that there is a difference in the average prosocial behavior of students between the Pre Test and Post Test, which means that there is an influence of the use of digital storytelling on student's prosocial behavior at As Salam Elementary School, Bangkalan Regency. Furthermore, the recommendations is to provide digital storytelling activities for elementary school-aged children, both at home and at school. Parents can provide digital storytelling at home. Meanwhile at school, teachers can use digital storytelling as a learning method given to fifth grade elementary school students.